A misdiagnosis of choledochal cyst type IB and recommendation to use gold-standard imaging techniques: a case report - Hyder, Arsalan; sharma, Nitik; Ali, Farhan; Sadiq, Hina; Ali, Kashif; Kumar, Hittik (Journal of the Pakistan Medical Association, 2022)
Abstract A choledochal cyst (CC) is a rare congenital dilation of the biliary ductal system that can cause troublesome complications when left untreated. CC in children classically manifests as a rare triad of the right upper quadrant mass, jaundice, and abdominal pain. Here, we report the case of an eight-year-old boy seen in Paediatric Unit I of Dr Ruth K. M. Pfau Civil Hospital Karachi, Pakistan, on October 9, 2019, who was initially misdiagnosed for liver abscess due to the non-specific symptoms and managed appropriately with antibiotics, which failed to improve the symptoms. Moreover, a hydatid cyst was considered based on ultrasonography (USG) which was later ruled out by the negative serology. A definitive diagnosis of CC was established on magnetic resonance cholangiopancreatography (MRCP). In resource-limited countries, USG is always the first line screening tool for biliary duct abnormalities which in some cases is comprehensibly enough for ----Continue---